Hubungan Dukungan Orang Tua dengan Kemandirian Belajar Siswa MI NW Birrul Walidain Rensing di Era Kurikulum Merdeka - Syamsur Rizal (Jurnal Ilmu Pendidikan, 2026)
The implementation of the Merdeka Curriculum requires students to possess independent, active, and responsible learning abilities in the learning process. However, in practice, many students still demonstrate a high level of dependence on teachers and parents in completing academic tasks. One of the factors presumed to be associated with students’ learning independence is parental support. This study aimed to determine the relationship between parental support and students’ learning independence at MI NW Birrul Walidain Rensing in the 2024/2025 academic year within the context of the Merdeka Curriculum. This study employed a quantitative approach with a correlational research design. The population consisted of all students at MI NW Birrul Walidain Rensing, while the sample was selected using a simple random sampling technique. Data were collected through Likert-scale questionnaires that had been tested for validity and reliability. Data analysis techniques included descriptive statistics and Pearson Product Moment correlation analysis using SPSS. The findings revealed a positive and significant relationship between parental support and students’ learning independence, with a correlation coefficient value of 0.742 and a significance value of 0.000 < 0.05. These results indicate that higher parental support is associated with higher levels of students’ learning independence. Therefore, parental involvement plays a crucial role in supporting the success of student learning within the implementation of the Merdeka Curriculum.